Can Access to Data Prevent Army Suicides? - Ramchand, Rajeev; Kelly, Theresa F. (RAND Corporation, 2023)
The U.S. Army is developing a system to inform leaders of individual- and unit-level suicide risk factors and to support prevention and intervention activities. One shortfall of this approach is the lack of guidance on how Army leaders should interpret and use this information. To address this gap, RAND Arroyo Center convened a group of experts to reach consensus on recommended actions for leaders and the data needed to support those actions.